2021
DOI: 10.35484/pssr.2021(5-i)48
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Professional Development: Performance of Primary School Teachers

Abstract: The purpose of this study was to examine the performance of primary school teachers (PSTs) under the Continuous Professional Development (CPD) framework. The study was conducted in the district Faisalabad of the Punjab Province. Both qualitative and quantitative methods were used in combination as a mixed methods approach to solve the research problem. Secondary data of mentoring visit forms (MVF) filled by the District Teacher Educators (DTEs) were analyzed to assess the performance of the PSTs. To get the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Despite the comprehensive attention given to teachers' training and professional development within educational policies and reforms since 2000, the quality of education in public schools continues to face substantial disapproval. This could stem from inadequacies in executing policy decisions and shortcomings in implementing teachers' professional development initiatives (Munir, 2020). Teacher professional development (TPD) in our country typically involves attending externally organized training events such as workshops, conferences, seminars, or meetings, usually coordinated by the central office or other external bodies (DSD, 2006;2007a;Mohammad, 2004;Zareen, Mahmood, & Mahmood, 2013).…”
Section: State Of Continuous Professional Development In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the comprehensive attention given to teachers' training and professional development within educational policies and reforms since 2000, the quality of education in public schools continues to face substantial disapproval. This could stem from inadequacies in executing policy decisions and shortcomings in implementing teachers' professional development initiatives (Munir, 2020). Teacher professional development (TPD) in our country typically involves attending externally organized training events such as workshops, conferences, seminars, or meetings, usually coordinated by the central office or other external bodies (DSD, 2006;2007a;Mohammad, 2004;Zareen, Mahmood, & Mahmood, 2013).…”
Section: State Of Continuous Professional Development In Pakistanmentioning
confidence: 99%
“…The United States invests nearly $18,000 per teacher annually and dedicates 19 days of teacher time to yearly training (TNTP, 2015). Munir (2020) found that in Pakistan, Continuing Professional Development (CPD) in education remains a relatively new concept, with limited literature available locally on the subject. There needs to be a significant knowledge gap in comprehending the true worth of teacher development through mentoring within the CPD framework.…”
Section: Introductionmentioning
confidence: 99%